Losing Control: The Erosion of Disciplinary and Pastoral Power in Accounting Firms - Couchoux, Oriane; Daoust, Laurence; Malsch, Bertrand (Contemporary Accounting Research, 2026)
ABSTRACT Accounting firms have traditionally operated as both elite and reinventive institutions that offer a structured and prestigious career path and enforce a deeply transformative socialization process for auditors. However, recent labor market shifts and evolving work preferences are challenging this regime of power, with significant implications for firms and their employees. Drawing on 31 semistructured interviews with auditors in Canada, our study examines how these changes are reshaping power dynamics within accounting firms. First, we find that firms are increasingly struggling to define and produce the ideal auditor. Instead, as we highlight, they are experiencing the emergence of the default auditor , a professional shaped more by labor market constraints and transactional engagement than by traditional firm‐driven selection and disciplinary mechanisms. Second, we analyze the erosion of pastoral power (i.e., power rooted in guidance and care) within firms, as staff auditors prioritize the care of the self, while partners and managers (P&Ms) increasingly struggle to establish and sustain pastoral relationships with their subordinates. As a result of this erosion, P&Ms fluctuate between self‐sacrifice (i.e., taking on additional responsibilities to compensate for auditors' disengagement) and a growing sense of inequity (i.e., feeling they are giving too much while receiving too little in return). To capture this growing impasse, we develop the concept of disciplinary and pastoral paralysis , a state in which P&Ms can no longer rely on traditional mechanisms of discipline and punishment to enforce norms of professional conduct but also struggle to reinvent new forms of pastoral power. We examine the implications of this loss of control, questioning whether it represents a temporary shift or a more permanent transformation. Finally, we discuss the broader consequences of accounting firms becoming less like normalizing institutions and more like “ normal ” organizations.